Clinical features, molecular results, and management of 12 individuals with the rare arthrochalasia Ehlers‐Danlos syndrome. Issue 5 (24th February 2020) - Ayoub, Sandy; Ghali, Neeti; Angwin, Chloe; Baker, Duncan; Baffini, Stella; Brady, Angela F.; Giovannucci Uzielli, Maria Luisa; Giunta, Cecilia; Johnson, Diana S.; Kosho, Tomoki; Neas, Katherine; Pope, F. Michael; et al.
Abstract: Arthrochalasia Ehlers‐Danlos syndrome (aEDS) is a rare autosomal dominant connective tissue disorder that is characterized by congenital bilateral hip dislocations, severe generalized joint hypermobility, recurrent joint (sub)luxations, and skin hyperextensibility. To date, 42 patients with aEDS have been published. We report 12 patients with aEDS from 10 families with 6 unpublished individuals and follow‐up data on 6 adult patients. The clinical features are largely comparable with patients reported in the literature. Most ( n = 10) patients had variants leading to (partial) loss of exon 6 of the COL1A1 or COL1A2 genes. One patient did not have a previously reported likely pathogenic COL1A1 variant. Data regarding management were retrieved. Hip surgery was performed in 5/12 patients and 3/12 patients underwent spinal surgery. As much as 4/12 patients were wheelchair‐bound or unable to walk unaided. Fractures were present in 9/12 individuals with 1 patient requiring bisphosphonate treatment. Echocardiograms were performed in 10 patients and 2 individuals showed an abnormality likely unrelated to aEDS. One patient gave birth to two affected children and went through preterm labor requiring medication but had no additional complications. Of the eight adults in our cohort, the majority entered a career. Our data point toward a genotype–phenotype relationship with individuals with aEDS due to pathogenic COL1A1 variants causing complete or partial loss of exon 6 being more severely affected regarding musculoskeletal features. There is a significant lack of knowledge with regard to management of aEDS, particularly in adulthood. As such, systematic follow‐up and multidisciplinary treatment is essential.